Indonesia-China’s Diplomatic Relations after Normalization in 1990 - Ahmad Syaifuddin Zuhri (Proceeding Of The International Seminar and Conference on Global Issues, 2015)
This research is studying about Indonesia-China’s diplomatic relations after normalization in 1990. The long troubled diplomatic relations between Indonesia and China becomes an interesting background in analyzing their recent relations. As the current relation between Indonesia and China is getting closer, in line with the increase of Chinese economic power; it is interesting to discover the win-win cooperation offered by China. Keywords: Indonesia, China, Diplomatic Relations